Une destination « non touristique » à la mode : la région d’Aysén, en Patagonie chilienne - Franck Michel (Études Caribéennes)
The territory of Aysen in southern Chile, officially called "Region XI" has the discreet charm of a forgotten Patagonia. This legendary region has haunted the fertile imagination of explorers and travelers of all kinds. Today, they are so many rich fly fishermen that European or Israeli backpackers, and always more Chileans coming from the middle class and from the north of the country. Patagonia is a wonderful playground, and even more a vast space of utopia, then as now, for many travelers and dreamers.The "charm" is undeniable, simply contemplate the fabulous nature clearly dominating culture here, and the area is not a paradise for photographers by chance. As to the character "discrete", it is also clear, as evidenced by many tourists in search of their own experience "into the wild" and marvel treading the beaten path not of Patagonia. Playground for adventurers, place of science for researchers, refuge area for fortunate expatriates testing ground if not some rite of passage for young athletes, walkers, cyclists or loafers, Chilean Patagonia is now mostly become an issue, and therefore economic policy, rather essential for the country.This article, the first result of a work in progress, brings some elements to try to understand how to manufacture and settled in time and space, "a non-tourist destination", which, in recent years, the for the media but not only has the wind in its sails. With or without the consent of all the habitants of Patagonia? This is the real challenge ahead.